Corposmídia em traje de cena: desafios para criar/pensar/mover figurinos e figurinistas no cinema - Imparato, Joana (2019)
Taking into consideration the misunderstandings and lacunae in the education of cinema costume designers in Brazil, this research aims to discuss how costume designer practice may find new procedures to build coherent costume designs considering the complexity and singularities which relates body and environment from an epistemological changes perspective in the last three decades. The research was done investigating costume design discipline syllabus in undergraduate, postgraduate and extension courses in universities, as well as other courses in the area, offered in Brazil between January 2018 and June 2019. The goal was to check how body is or is not presented in formal costume design studies in the country. Its methodological basis is supported by the selection, grouping, investigation and comparison of courses and syllabus, in the discussion of body notion and in the proposition of an alternative for the creative process. The theoretical reference considers the concept of corpusmedia developed by Greiner and Katz (2005, 2010, 2016) and relations between fashion and subjectivity investigated by Mesquita (2004). The study hypothesis is that from corpusmedia concept it is possible to bring complexity to creative film design costume process through methodological procedures to start other relations between reality and fiction, movements and images, perceptions and actions